2008
DOI: 10.1183/09031936.00111808
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomographic emphysema distribution: relationship to clinical features in a cohort of smokers

Abstract: Computed tomography (CT) scanning allows precise assessment of both the extent and distribution of emphysema. There has been little work on the relationship between the distribution of emphysema and clinical features of the disease. The current study investigated the association between clinical features and distribution of emphysema.A total of 129 patients with smoking-related chronic obstructive pulmonary disease underwent CT assessment of the extent and distribution of their emphysema (core/rind and upper/l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
1
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 24 publications
3
41
1
2
Order By: Relevance
“…Analysis of emphysema distribution in COPD patients (FEV 1 % predicted 52 6 19) revealed a predominance of chances in the upper and core regions of the lung (49). Increased core distribution was associated with lower FEV 1 , FEV 1 /FVC ratio, and body mass index (BMI).…”
Section: Quantitative Analysismentioning
confidence: 99%
“…Analysis of emphysema distribution in COPD patients (FEV 1 % predicted 52 6 19) revealed a predominance of chances in the upper and core regions of the lung (49). Increased core distribution was associated with lower FEV 1 , FEV 1 /FVC ratio, and body mass index (BMI).…”
Section: Quantitative Analysismentioning
confidence: 99%
“…All scans were evaluated centrally at the University of Edinburgh. Emphysema was quantified as the percentage of lung CT voxels below a threshold of −950 Hounsfield Units-% low attenuation areas (LAA)-950, using the software Pulmonary Workstation 2.0 (VIDA Diagnostics, Iowa City, IA, USA) as described previously [13][14][15]. MMP-9 ELISA and MMP-9 activity kits (fluorescence resonance energy transfer (FRET) method) were supplied by R&D Systems Europe Ltd. (Cat.…”
Section: Measurementsmentioning
confidence: 99%
“…Mair et al [20] analyzed variables that might predict the severity of emphysema and found that BMI was the best predictor. In our patient population, we found a strong inverse correlation between BMI and extend of emphysema that is in correlation the knowledge that BMI is tightly associated with emphysema, at least in patients with normal BMI and diffuse emphysema.…”
Section: Discussionmentioning
confidence: 99%